2011
DOI: 10.1016/j.watres.2010.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of adenoviruses and noroviruses in European recreational waters

Abstract: Exposure to human pathogenic viruses in recreational waters has been shown to cause disease outbreaks. In the context of Article 14 of the revised European Bathing Waters Directive 2006/7/EC (rBWD, CEU, 2006) a Europe-wide surveillance study was carried out to determine the frequency of occurrence of two human enteric viruses in recreational waters. Adenoviruses were selected based on their near-universal shedding and environmental survival, and noroviruses (NoV) selected as being the most prevalent gastroente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 238 publications
(104 citation statements)
references
References 59 publications
7
84
0
1
Order By: Relevance
“…No JCPyV was detected in marine samples collected in winter. The lower frequency of HAdV and JCPyV in seawater was consistent with other studies that suggested marine dispersion, dilution and disinfection due to the high salinity may be the cause of the low concentrations reported (Hawley and Garver, 2008;Wyn-jones et al, 2010).…”
Section: Occurrence Of Viral Pathogens and Indicator Microorganisms Isupporting
confidence: 91%
“…No JCPyV was detected in marine samples collected in winter. The lower frequency of HAdV and JCPyV in seawater was consistent with other studies that suggested marine dispersion, dilution and disinfection due to the high salinity may be the cause of the low concentrations reported (Hawley and Garver, 2008;Wyn-jones et al, 2010).…”
Section: Occurrence Of Viral Pathogens and Indicator Microorganisms Isupporting
confidence: 91%
“…Africa12.5% (3/24) to 23.8% (5/21)4.8% (1/21) to 23.5% (25/106)2.9 (1.7–3.3)2.6 (2.0–2.9)Mans et al (2013)S. Korea20.0% (5/25)56.0% (14/25)Park et al (2011)Netherlands15.0% b Wyn-Jones et al (2011)UK10.0% b Wyn-Jones et al (2011) a Log 10 genome copies or viral particles per litre of water b Number of samples not stated …”
Section: Nov Abundance and Distribution In Estuarine And Coastal Watersmentioning
confidence: 99%
“…Some human viruses may be used as indicators of viral contamination (Pina et al, 1998; Albinana et al, 2009; Wyn-Jones et al, 2011). The strongest candidates seem to be adenovirus (AdV), norovirus (NV), and enterovirus (EV); polyomavirus was also suggested (McQuaig et al, 2009).…”
Section: Introductionmentioning
confidence: 99%